Inducing and Aggravating Factors of Gastroesophageal Reflux Symptoms - Radhiyatam Mardhiyah; Ari Fahrial Syam; Siti Setiati (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Gastroesophageal reflux disease (subsequently abbreviated as GERD) is a  disease commonly found in the community. Several factors have been recognized as inducing and aggravating factors of GERD symptoms such as older age, female gender, obesity, smoking habit, alcohol consumption, certain diet and poor eating habit like eating fatty, spicy, and acid food.